2010
DOI: 10.1080/13562517.2010.507301
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning across disciplines: student and staff experiences in a newly modularised system

Abstract: This is an electronic version of an article published in Teaching in Higher Education, Volume 15, Issue 6 December 2010 , pages 675 -689, which is available online at: http://dx.doi.org/10.1080/13562517.2010.507301 This is an electronic version of an article published in Teaching inHigher Education, Volume 15, Issue 6 December 2010 , pages 675 -689, which is available online at: http://dx.doi.org/10.1080/13562517.2010.507301 2 AbstractWithin modular degrees it is sometimes possible for students to broaden the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The results of the study revealed that the most important criterion that determines pre-service and inservice EFL teachers' preferences of the GK elective courses is their 'personal needs and interests' with a frequency of 628 (57.5%) among 1093 participants. The study has the same findings with Daly and Last (2017), Hennessy, Hernandez, Kieran, and McLoughlin (2010), Palmer, Burke, and Aubusson (2017), Purcell, Dunnion, and Loughran (2010), Sabir, Ahmad, Ashraf, and Ahmad (2013), Samara (2015), Stiles-Clarke and MacLeod (2016), Tezcan and Gümüş (2008) and Ulusoy et al (2012)'s studies in which participants stated their needs or interests as one of the important determinants in choosing a course. As students enroll in many courses throughout their education and these courses are mostly compulsory, they can make the most of the opportunity and choose as they wish when they are given a chance.…”
Section: Discussionsupporting
confidence: 78%
“…The results of the study revealed that the most important criterion that determines pre-service and inservice EFL teachers' preferences of the GK elective courses is their 'personal needs and interests' with a frequency of 628 (57.5%) among 1093 participants. The study has the same findings with Daly and Last (2017), Hennessy, Hernandez, Kieran, and McLoughlin (2010), Palmer, Burke, and Aubusson (2017), Purcell, Dunnion, and Loughran (2010), Sabir, Ahmad, Ashraf, and Ahmad (2013), Samara (2015), Stiles-Clarke and MacLeod (2016), Tezcan and Gümüş (2008) and Ulusoy et al (2012)'s studies in which participants stated their needs or interests as one of the important determinants in choosing a course. As students enroll in many courses throughout their education and these courses are mostly compulsory, they can make the most of the opportunity and choose as they wish when they are given a chance.…”
Section: Discussionsupporting
confidence: 78%
“…Identifying different motivations behind the choice of elective modules has been the subject of several empirical studies, but these studies tend to investigate at the programme level rather than at the module level. For example, Hennessy et al (2010), Howorth (2001) and Koceic et al (2010) analysed the reasons for choosing programme and non-programme electives by specialist and non-specialist students and identify both intrinsic and extrinsic motivations. They suggested that a deep learner may adopt a surface learning strategy when the system encourages them to choose a module that they perceive to be much easier than others but not necessarily of interest.…”
Section: Modules Majors Programmes and Universitiesmentioning
confidence: 99%
“…However, modular education may also reduce high school dropout through an arguably undesirable mechanism. Moreover, Hennessy et al (2010) estimated that 46.4% of the surveyed students opted for a particular module because they thought it would be an easy option. This problem was recognised by Rust (2000), who found that pupils tend to enroll into modules just to 'tick them off' instead of gaining additional knowledge about a topic.…”
Section: Modular Education May Influence High School Dropoutmentioning
confidence: 99%
“…This problem was recognised by Rust (2000), who found that pupils tend to enroll into modules just to 'tick them off' instead of gaining additional knowledge about a topic. Moreover, Hennessy et al (2010) estimated that 46.4% of the surveyed students opted for a particular module because they thought it would be an easy option. Although this theoretical mechanism predicts that modular education may reduce high school dropout, it may also lead to a drop in educational quality.…”
Section: Modular Education May Influence High School Dropoutmentioning
confidence: 99%